Fixed Point Theorems for New Type Contractive Mappings. (2nd June 2019) - Sezen, Müzeyyen Sangurlu
Abstract : In this paper, we introduce some new concepts of contractions calledγ - contractions andγ - weak contractions. We prove some fixed point theorems for mappings providingγ - contractions andγ - weak contractions unlike known results in the literature. Also, we present a few examples to illustrate the validity of the results obtained in the paper.